2003
DOI: 10.1016/s0955-2219(02)00413-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature, ripening time and calcination on the morphology and crystallinity of hydroxyapatite nanoparticles

Abstract: Nano-sized hydroxyapatite (HA) particles were prepared by chemical precipitation through aqueous solutions of calcium chloride and ammonium hydrogenphosphate. The influence of temperature, ripening time and calcination on the crystallinity and morphology of the HA nanoparticles were investigated. It was found that the crystallinity and crystallite size increased with the increase of synthetic temperature and ripening time. XRD and TEM results showed that the morphology change of HA nanoparticles was related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
196
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(210 citation statements)
references
References 28 publications
(28 reference statements)
12
196
0
2
Order By: Relevance
“…Therefore, mass loss in this range of temperature is larger compared to that for pure hydroxyapatite described by Skwarek et al [19]. In the temperature range 200-950°C, small mass loss results from removal of carbonates and chemically bonded water [20,21]. These data are in agreement with the results obtained by Bianco et al [22].…”
Section: Adsorption Of Oxalate Ionssupporting
confidence: 90%
“…Therefore, mass loss in this range of temperature is larger compared to that for pure hydroxyapatite described by Skwarek et al [19]. In the temperature range 200-950°C, small mass loss results from removal of carbonates and chemically bonded water [20,21]. These data are in agreement with the results obtained by Bianco et al [22].…”
Section: Adsorption Of Oxalate Ionssupporting
confidence: 90%
“…Therefore, different production methods were reported such as mechanochemistry [3,4], ultrasonic irradiation [5], microwave irradiation [6,7], sol-gel [8][9][10][11], chemical precipitation [12,13], hydrothermal method [14][15][16], hydrolysis [17], microemulsion [18][19][20], and emulsion liquid membrane [21]. The synthesized HAp does not have adequate biological properties as the natural apatite existing in bones.…”
Section: Introductionmentioning
confidence: 99%
“…The result indicated 45.96% increase in the crystallite size of treated compound as compared to the control sample. Pang and Bao reported that due to synthesis temperature and ripening on hydroxyapatite causes an increase in crystallite size [31]. Rey et al [32] and Drouet et al [33] reported an increase in crystal size with increase in temperature and pH.…”
Section: X-ray Diffractionmentioning
confidence: 99%